2001
DOI: 10.1073/pnas.221582098
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide antibiotic biosynthesis: Enzymatic assembly of the dedicated amino acid monomer ( S )-3,5-dihydroxyphenylglycine

Abstract: Four proteins, DpgA-D, required for the biosynthesis by actinomycetes of the nonproteinogenic amino acid monomer (S)-3,5-dihydroxyphenylglycine (Dpg), that is a crosslinking site in the maturation of vancomycin and teicoplanin antibiotic scaffolds, were expressed in Escherichia coli, purified in soluble form, and assayed for enzymatic activity. DpgA is a type III polyketide synthase, converting four molecules of malonyl-CoA to 3,5-dihydroxyphenylacetyl-CoA (DPACoA) and three free coenzyme A (CoASH) products. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 29 publications
(49 reference statements)
2
117
0
6
Order By: Relevance
“…VemA–F are homologues of Ken2–7, which have been proposed to catalyse the formation of the 3,5‐dihydroxybenzoic acid starter unit utilised by a type I modular PKS for the assembly of kendomycin in Streptomyces violaceoruber 20. VemA has 60–70 % identity to DpgA, a type III PKS that has been shown to catalyse the conversion of four malonyl‐CoA molecules to (3,5‐dihydroxyphenyl)acetyl‐CoA 21. VemB and VemD are homologues of DpgB and DpgD, respectively, which have been shown to increase the efficiency of the DpgA‐catalysed reaction 21.…”
Section: Resultsmentioning
confidence: 99%
“…VemA–F are homologues of Ken2–7, which have been proposed to catalyse the formation of the 3,5‐dihydroxybenzoic acid starter unit utilised by a type I modular PKS for the assembly of kendomycin in Streptomyces violaceoruber 20. VemA has 60–70 % identity to DpgA, a type III PKS that has been shown to catalyse the conversion of four malonyl‐CoA molecules to (3,5‐dihydroxyphenyl)acetyl‐CoA 21. VemB and VemD are homologues of DpgB and DpgD, respectively, which have been shown to increase the efficiency of the DpgA‐catalysed reaction 21.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the three gene products DpgB-D are required to convert the reaction product of DpgA into the amino acid Dpg. Enzymatic assays with the protein expressed in S. lividans showed that DpgA uses malonyl-CoA as the sole substrate to synthesize DPA-CoA (31,32).…”
Section: Bacterial Type III Pkssmentioning
confidence: 99%
“…The THNS from S. griseus (also known as RppA) has been shown to possess broad substrate specificity to yield a wide variety of products (20). In several strains that produce vancomycin group of natural products, a CHS-like protein performs the biosynthesis of 3,5-dihydroxyphenylglycine by using several molecules of malonyl-CoA as substrate (21)(22)(23). The precursor to the broad spectrum antimicrobial agent 2,4-diacetylphloroglucinol is produced by a CHS homologue (phlD) in many strains of fluorescent Pseudomonas sp.…”
mentioning
confidence: 99%